(untitled) (Journal of the College of Basic Education, 2026)
The research aims to identify the effect of the Structured Academic Debate Strategy on prospective memory among first-grade intermediate female students in governmental daytime secondary and intermediate schools affiliated with the Directorate of Education / Baghdad Al-Karkh First – Abu Ghraib Section. The researchers intentionally selected (Al-Ikhlas Secondary School for Girls) as the research sample. Then, two sections out of three first-grade intermediate sections were randomly chosen: Section (A) represented the experimental group, consisting of (37) students, who were taught according to the Structured Academic Debate Strategy; and Section (B) represented the control group, consisting of (36) students, who were taught according to the traditional method. Thus, the total research sample consisted of (73) students. The two groups were equated in a number of variables, namely: chronological age, previous academic achievement in science, a prior knowledge test, the Otis–Lennon Mental Ability Test, and prospective memory. As for the research instrument, the researcher constructed a Prospective Memory Scale based on the definition of Altgassen et al. (2017), which comprises three domains and consists of (24) items.After administering the scale, the results showed a statistically significant difference at the (0.05) level between the mean scores of the experimental group students who studied according to the Structured Academic Debate Strategy and the mean scores of the control group students who studied according to the traditional method, in favor of the experimental group. In light of these findings, a set of recommendations and conclusions was proposed